EFFECTIVENESS OF SUBSTANTIVE TECHNICAL EDUCATION AND TRAINING FOR ISLAMIC SENIOR HIGH SCHOOL BIOLOGY TEACHERS - Saputro, Budiyono; Lestari, Budi; Widiyanti, Fenny; Saputra, Heru (Department of Integrated Science, Faculty of Mathematics and Natural Sciences, Universitas Negeri Semarang in Collaboration with Perkumpulan Pendidikan IPA Indonesia, 2019)
The purpose of this study was to determine the effectiveness of substantive technical education and training program for Islamic High School (Madrasah Aliyah/MA) throughout Central Java and Yogyakarta. Quantitative research with